Pelatihan dan Motivasi Kerja terhadap Produktivitas Kerja Karyawan Departemen Produksi Section Stamping PT. Xyz di Karawang - Rheina Dhea Fitriani; Mochamad Vrans Romi (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the effect of training and work motivation on employee work productivity in the stamping section production department of PT. XYZ. The research method used is a quantitative approach based on the philosophy of positivism, involving 35 employee respondents and 1 manager as a direct superior. The data collection technique was carried out by distributing questionnaires using a semantic differential scale, and the data was analyzed with the help of the SPSS version 27 program through validity, reliability, multiple linear regression, and classical assumption tests. The results of the community service show that training is quite effective, with the trainer qualification sub-variable getting the highest score, while the training method is the lowest. Work motivation is relatively low, with responsibility as the highest sub-variable and recognition as the lowest. Work productivity is in the sufficient category, based on the assessment of the direct superior. Partially, training has a significant positive effect on work productivity, while work motivation does not have a significant effect. However, simultaneously, training and work motivation together affect work productivity. The conclusion of this activity shows that increasing the effectiveness of training and work motivation strategically can be the key to increasing employee productivity in the industrial work environment.  Keywords: Training, Work Motivation, Productivity